TINJAUAN YURIDIS PELAKSANAAN PUTUSAN PENGADILAN AGAMA MENGENAI TANGGUNG JAWAB AYAH TERHADAP ANAK SETELAH PERCERAIAN - Laode Muhammad Sayyid Amwal; Muhammad Syarifuddin; Rachmat Taibu (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
Formulation of the problem in this research: 1. What is the responsibility of the father to the child after divorce?, 2. What is the legal witness for the father who does not carry out his responsibilities?. The purpose of this study was to determine the responsibility of fathers to children after divorce. This research is a type of normative legal research which is a systematic study of law. The location of the research was carried out at the Baubau Religious Court. The type of data used is through literature study in the form of books, laws and regulations, documents, and so on. Analysis of the data used is content analysis, which is then presented descriptively in order to provide a clear understanding of the results of research conducted by the author. The results of this study indicate that the father's responsibility after the divorce is to provide maintenance and education costs that the child needs, and legal sanctions for fathers who do not carry out their obligations to support the child after the divorce are by confiscation of movable and immovable objects belonging to the ex-husband to replace child support costs that are not given to their children.